Rethinking public accounting policy and practice of accrual accounting in government - Das, S. K., 1945- (New Delhi ; Oxford : Oxford University Press, 2006)
In recent years, efficiency and accountability are receiving special emphasis in evaluating the role of government. The book argues for reforms in India's accounting system that can help set performance standards and be able to provide reliable information to monitor government expenditure.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Finance, Public -- India -- Accounting; Accrual basis accounting -- India